The PRESTO report. Sustainability and Resilience in the Irish Health System - Burke, Sara; Thomas, Stephen; O'Donoghue, Catherine (Trinity College Dublin/London School of Economics/Partnership for Health System Sustainability & re, 2023)
The recovery of the Irish health system from the COVID-19 pandemic provides an opportunity for reflection and learning. COVID-19 has tested health systems in the extreme and spotlighted long- standing weaknesses. This report assesses the resilience and sustainability of the Irish health system through its recent performance during the COVID-19 era, highlighting immediate and long- term challenges and opportunities. The report is not a critique of the government's response to COVID-19, as this would require a different approach and analyses. Nevertheless, it contains data that might be usefully fed into such an evaluation when it is conducted. Health system resilience and sustainability are not restricted to one crisis, however large and influential COVID-19 has been. The next shock, which may already be taking the form of a cost-of- living crisis fuelled by war in Ukraine and supply chain problems, will be very different. Therefore, it is important to build on the Irish health system’s ability to handle shocks during difficult periods of health and economic turmoil. This report seeks to present lessons and related recommendations resulting from analysis of available data and collective reflection by stakeholders on key issues.
PUBLISHED
Keywords: Inclusive Society; Making Ireland; Health systems research; health systems and policy; Chronic Health Condition; Accessibility